Crystal structure of chlorido-(O-ethyl phenylcarbamothioamide-κS)-bis(triphenylphosphane-κP)-silver(I), C45H41AgClNOP2S - Yeo, Chien Ing *; Liew, Li Yuan *; Chew, Jactty *; Teow, Sin Yeang *; Tiekink, Edward R. T. * (De Gruyter Open, 2020)
C45H41AgClNOP2S, monoclinic, P21/c (no. 14), a = 10.1930(3) Å, b = 18.3087(6) Å, c = 21.3088(6) Å, β = 94.516(3)°, V = 3964.3(2) Å3, Z = 4, Rgt(F) = 0.0353, wRref(F2) = 0.0810, T = 100(2) K.